A STRUCTURED LITERATURE REVIEW ON IMPULSE BUYING: ONLINE JITTERS AND OFFLINE JEEPERS - Hussain, Ammar; Ali, Zaigham; Ullah, Mehfooz; Rasool, Faiz (Humanities & Social Sciences Reviews, 2021)
Purpose of the Study: This structured literature review looks at Impulse Buying Behaviour in both virtual and brick-and-mortar contexts. The purpose of the study was to identify, evaluate, and synthesize the relevant research results to develop an abstract of current evidence by using unambiguous procedures to find what can consistently be said based on these researchers that can play a role in evidence-based practice. Furthermore, this systematic review aimed to minimize the bias resulting in other methods of reviewing research literature. Methodology: An appropriate sample of papers was collected via a systematic search. The initial stage of a systematic literature review involves identifying the academic papers from EBSCO, Emerald Full text, and Scopus that are most influential and relevant to online impulse buying behaviour. The next step was to refine the results to identify research studies that best match the research objectives. Main Findings: An interesting outcome of this paper has been that virtual impulse buying behaviour is quite similar to that of the offline context. Their mood influences customers when a potential purchase, their traits, and the shopping space (website) where the purchase is happening. The real difference between the virtual and offline context appears to be linked to spatial-temporal factors affected by the constraints of the virtual environment in which the e-retailers operate and impact customer mood Impulse Buying Tendency. Applications of this study: This literature review will help researchers map various approaches regarding the same research topic by bringing together various theoretical viewpoints. This study will also provide evidence of various approaches used by researchers while studying impulse buying behaviour through differentiating distinctive research methods used to respond to the same research questions. Novelty/Originality of this study: For so many years' researchers are trying to find effective approaches to formulate the influencing elements to increase impulse buying. A review of the literature has been done to make the reader understand the elements of impulse buying behaviour regarding offline and online settings. The study also provides the conceptual framework of impulse buying and its factors.